ERP and E-Business Application Deployment in Open Source Distributed Cloud Systems - George SUCIU; Traian-Lucian MILITARU; Gyorgy TODORAN (Database Systems Journal, 2012)
In this paper we present the way in which we combine SlapOS, the fist open source operating system for distributed cloud computing, and Enterprise Resource Modeling (ERP) to provide an simple, unified API for E-Business Applications based on Iaas, PaaS and SaaS models. SlapOS is based on a grid computing daemon – called slapgrid – which is capable of installing any software on a PC and instantiate any number of processes of potentially infinite duration of any installed software using a master-slave model. SlapOS Master follows an ERP model to handle at the same time process allocation optimization and billing.